Prediksi Harga Saham menggunakan Metode Backpropagation dengan Optimasi Ant Colony Optimization - David Bernhard; Muhammad Tanzil Furqon; Muh. Arif Rahman (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Stocks are a sign of a person's or party's investment contribution to a company or limited liability company. Movement of stock prices affects the profits and losses that will be obtained by the investor. The obstacle is stock prices can change in every minute on weekdays. It takes a method that is able to predict stock prices accurately and consistently, so that it can minimize the risk of stock investment. Besides its advantages, BPNN has shortcoming, such as slow convergence time, easy convergence to local minimum points, and poor generalization capabilities. ACO has advantages in distributed computing, positive feedback, and metaheuristic properties that can improve the weaknesses of BPNN. This study uses time series data from the stock price of Bank Rakyat Indonesia (Persero) Tbk. period 1 January 2018 until 31 December 2018. ACO serves to optimize the value combination of learning rate, momentum, and number of hidden nodes for BPNN training phase. Best combination of ACO parameter values was obtained, namely the ant cycle constant worth 0.8, the control constant of pheromone intensity worth 0.1, the visibility control constant worth 0.1, the local pheromone evaporation constant worth 0.5, global pheromone evaporation constant worth 0.1, number of ants 5, and number of iterations 7. That combination produces an average of MAPE 1.745, while BPNN only reached 3.024.